Pengaruh Penggunaan Media Software Simurelay dalam Meningkatkan Kemampuan Berpikir Komputasional dan Kreativitas Peserta Didik - Annas Khoir Dwi Nikmaturrohman; Joko Joko; Tri Rijanto; Yulia Fransisca (Indo Publishing, 2026)
This study examines the effect of Simurelay software-based learning media on students’ computational thinking skills and creativity in the context of Electric Motor Installation subject at vocational secondary school. A quasi-experimental design with a Nonequivalent Control Group Design was employed involving 60 tenth-grade students (TITL) at SMKN 1 Driyorejo, divided equally into an experimental group using Simurelay (n = 30) and a control group using PowerPoint (n = 30). Data were collected through validated pretest and posttest instruments and analysed using N-Gain scores, independent sample t-test, and MANOVA. Results indicate that Simurelay did not produce a statistically significant effect on computational thinking (Sig. = 0.708 > 0.05), whereas it yielded a significant effect on creativity (Sig. = 0.011 < 0.05). N-Gain scores for both variables were categorised as moderate in both groups. These findings suggest that simulation-based media is more appropriate for cultivating creativity through open-ended exploration, while the development of computational thinking demands more systematic, algorithm-oriented, and long-term pedagogical strategies.